2017
DOI: 10.3847/1538-3881/aa88b9
|View full text |Cite
|
Sign up to set email alerts
|

Average Albedos of Close-in Super-Earths and Super-Neptunes from Statistical Analysis of Long-cadence Kepler Secondary Eclipse Data

Abstract: We present the results of our work to determine the average albedo for small, close-in planets in the Kepler candidate catalog. We have adapted our method of averaging short cadence light curves of multiple Kepler planet candidates to long cadence data, in order to detect an average albedo for the group of candidates. Long cadence data exist for many more candidates than the short cadence, and so we separate the candidates into smaller radius bins than in our previous work: 1-2 R ⊕ , 2-4 R ⊕ , and 4-6 R ⊕ . We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…Typical visual geometric albedos of hot Jupiters are of the order of 0.1 (Schwartz & Cowan 2015) and are statistically lower than for hot super-Earths (Demory 2014) and Neptunes (Sheets & Deming 2017). According to the atmospheric models, the lower albedos may be attributed to the presence of alkali metals as well as TiO and VO in hotJupiter atmospheres, which causes significant absorption in the visual wavelengths (Demory et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Typical visual geometric albedos of hot Jupiters are of the order of 0.1 (Schwartz & Cowan 2015) and are statistically lower than for hot super-Earths (Demory 2014) and Neptunes (Sheets & Deming 2017). According to the atmospheric models, the lower albedos may be attributed to the presence of alkali metals as well as TiO and VO in hotJupiter atmospheres, which causes significant absorption in the visual wavelengths (Demory et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Cooler planets observed at shorter wavelengths (Shporer & Hu, 2015) are much more likely to yield precise albedo measurements. Finally, the geometric albedos of hot and warm ( T eq ≥ 600 K) Neptune‐size, mini‐Neptune, and rocky exoplanets in the Kepler bandpass have been constrained to low values (≤0.2) (Demory, 2014; Jansen & Kipping, 2018; Sheets & Deming, 2014, 2017). Though the large measurement uncertainties have prevented solid conclusions to be drawn about aerosol properties in their atmospheres, reflective, spatially extensive aerosols are unlikely.…”
Section: Insights From Observationsmentioning
confidence: 99%
“…However, 55 Cnc e should be compared to planets of its own size. Albedo measurements of the Kepler close-in super-Earth and Neptune sample as a whole have revealed that these worlds are somewhat less dark than hot Jupiters, but still have A g values generally below 0.3 (Demory 2014;Sheets & Deming 2017;Jansen & Kipping 2018). One exception is the hot rocky exoplanet Kepler-10b (Batalha et al 2011).…”
Section: Albedo Of 55 Cnc Ementioning
confidence: 99%